2014
DOI: 10.1074/jbc.m113.537282
|View full text |Cite
|
Sign up to set email alerts
|

Separate Intramolecular Targets for Protein Kinase A Control N-Methyl-d-aspartate Receptor Gating and Ca2+ Permeability

Abstract: Background: PKA increases NMDA receptor responses and phosphorylates multiple residues on C-terminal domains (CTD). Results: PKA inhibition reduced gating through GluN2B CTD and reduced Ca 2ϩ permeability through GluN1 CTD. Conclusion: PKA controls NMDA receptor gating and Ca 2ϩ permeability through distinct sites. Significance: Dissecting the complex modulatory effects of PKA on NMDA receptors helps delineate fundamental mechanisms of synaptic regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 48 publications
(70 reference statements)
1
31
0
1
Order By: Relevance
“…GluN1 CTD contains PKA phosphorylation sites that, in glutamatergic GluN1/GluN2 receptors, control the receptor’s calcium permeability [51]. To examine whether the C-terminal sequence of GluN1 subunits influences conductance and permeation properties for glycinergic GluN1/GluN3A receptors, we recorded whole-cell currents in response to glycine (0.5 mM) in the absence or presence of 1.8 mM free external Ca 2+ and varied the applied pipette potential between −80 mV and +60 mV in 20 mV increments.…”
Section: Resultsmentioning
confidence: 99%
“…GluN1 CTD contains PKA phosphorylation sites that, in glutamatergic GluN1/GluN2 receptors, control the receptor’s calcium permeability [51]. To examine whether the C-terminal sequence of GluN1 subunits influences conductance and permeation properties for glycinergic GluN1/GluN3A receptors, we recorded whole-cell currents in response to glycine (0.5 mM) in the absence or presence of 1.8 mM free external Ca 2+ and varied the applied pipette potential between −80 mV and +60 mV in 20 mV increments.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that LTD was not associated with a change in decay kinetics of EPSC NMDA , suggesting no change in NMDAR subunit composition in our experiments. PKA activity has been shown to enhance NMDAR function via phosphorylation of NR1, NR2A, and NR2B subunits (44)(45)(46); thus, a reduction in PKA activity and subsequent dephosphorylation of NMDARs may provide a potential mechanism underlying the decrease in NMDAR currents (44).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway has generally been viewed as linking extracellular signals to the synthesis of new proteins, especially of AMPA receptors, as well as to transcription regulation, thus participating in the late phase of LTP consolidation. Another pathway, which has received recent attention is the ability of PKA to phosphorylate various residues in GluN2B and GluN1 subunits of NMDA receptors, thereby regulating their gating properties or calcium permeability (Lau et al, 2009; Aman et al, 2014; Murphy et al, 2014). Finally, it is interesting to note that PKA is also involved in actin filament regulation.…”
Section: The Protein Kinase Cascadesmentioning
confidence: 99%